Origin of ecdysis: fossil evidence from 535-million-year-old scalidophoran worms. Issue 1906 (10th July 2019) - Wang, Deng; Vannier, Jean; Schumann, Isabell; Wang, Xing; Yang, Xiao-Guang; Komiya, Tsuyoshi; Uesugi, Kentaro; Sun, Jie; Han, Jian
Abstract : With millions of extant species, ecdysozoans (Scalidophora, Nematoida and Panarthropoda) constitute a major portion of present-day biodiversity. All ecdysozoans secrete an exoskeletal cuticle which must be moulted periodically and replaced by a larger one. Although moulting (ecdysis) has been recognized in early Palaeozoic panarthropods such as trilobites and basal groups such as anomalocaridids and lobopodians, the fossil record lacks clear evidence of ecdysis in early scalidophorans, largely because of difficulties in recognizing true exuviae. Here, we describe two types of exuviae in microscopic scalidophoran worms from the lowermost Cambrian Kuanchuanpu Formation ( ca 535 Ma) of China and reconstruct their moulting process. These basal scalidophorans moulted in a manner similar to that of extant priapulid worms, extricating themselves smoothly from their old tubular cuticle or turning their exuviae inside out like the finger of a glove. This is the oldest record of moulting in ecdysozoans. We also discuss the origin of ecdysis in the light of recent molecular analyses and the significance of moulting in the early evolution of animals.